Effect of cationic lipid type in PEGylated liposomes on siRNA delivery following the intravenous injection of siRNA lipoplexes. (2019) - HATTORI, YOSHIYUKI; NAKAMURA, MARI; TAKEUCHI, NOZOMI; TAMAKI, KYOKO; OZAKI, KEI-ICHI; ONISHI, HIRAKU
No abstract available